Knowledge Services : A Strategic Framework for the 21st Century Organization - Guy St. Clair (De Gruyter Saur, 2017)
Knowledge services converges information management, knowledge management (KM), and strategic learning into a single enterprise-wide discipline for the benefit of the business or organization in which it is practiced. As the acknowledged framework for strategic knowledge management, knowledge services—the responsibility of the knowledge strategist—leads to excellence in knowledge sharing and ultimately to shaping the organization as a knowledge culture. Knowledge Services: A Strategic Framework for the 21st Century Organization provides guidance for the knowledge strategist and is designed specifically to serve as a reference for that management employee, and for those seeking to become knowledge strategists.